When do Countries Benefit from Forming a Monetary Union? - Dominik Groll (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The New Keynesian DSGE literature has come to the consensus that, from the perspective of business cycle stabilization, countries are worse off in terms of welfare by forming a monetary union. This consensus, however, is based on the assumption of monetary policy being optimal. Using a standard two-country model, this paper shows that under suboptimal monetary policy, countries may gain in welfare by forming a monetary union, highlighting an important inherent benefit of fixing the exchange rate. Whether countries benefit from a monetary union depends primarily on the degree of price stickiness and how monetary policy is conducted: If prices are rather sticky and if monetary policy is not very aggressive towards inflation, forming a monetary union is beneficial. In contrast, asymmetries in the degree of price stickiness between countries are not of any importance for a monetary union to be welfare-enhancing or not.
Keywords: F41; F33; E52; 330